Given the equation ƒ(a) = a

Using the power rule, the derivative ƒ'(a) of aa

For this term, a = 1, n = 2, and a is the variable we derive in terms of

ƒ(a) = a

ƒ'(a) = (1 * 2)a

ƒ'(a) = 2a <--- Used in our final answer.

Using the power rule, the derivative ƒ'(a) of aa

For this term, a = -1, n = 1, and a is the variable we derive in terms of

ƒ(a) = -a

ƒ'(a) = (-1 * 1)a

ƒ'(a) = -1 <--- Used in our final answer.

Using the power rule, the derivative ƒ'(a) of aa

For this term, a = 6, n = 0, and a is the variable we derive in terms of

ƒ(a) = 6

ƒ'(a) = 0 <--- The derivative of a constant = 0. This is part of our answer.

ƒ'(a) =

ƒ'(0) = 2(0) - 1

ƒ'(0) = 2(0) - 1

ƒ'(0) = 0 - 1

ƒ'(0) =